Implementasi Program Kolega Sejati dalam Upaya Penguatan Pendidikan Karakter Berbasis Keluarga di Kota Bukittinggi - Thania, Tira; Sunarso, Sunarso (Universitas Negeri Malang, 2023)
The purpose of writing this article is to analyze the implementation of the Kolega Sejati program to strengthen family-based character education in the community in the city of Bukittinggi. The study uses a qualitative approach with a case study type. In the implementation of the Kolega Sejati program, it was found that there was a planning, implementation and evaluation process that overall had run optimally in terms of communication, bureaucratic structure, resources, and disposition. Internally, there is support from competent organizers, adequate infrastructure, and sufficient funds. Externally there is support in the form of collaboration with other parties, as well as support from the community. Internal obstacles are the organizers’ schedules which conflict with the main duties of the department, and external obstacles are weather obstacles and community support which is still uneven. The perceived impact of the Kolega Sejati program on strengthening family-based character education is the realization of the values of harmony, tolerance, piety, and a culture of healthy living